2016
DOI: 10.1186/s40317-016-0115-6
|View full text |Cite
|
Sign up to set email alerts
|

Generation of multistate release–recapture models using a graphic user interface (GUI)

Abstract: Background: Multistate release-recapture models are used to study the movements and survival of animals when multiple migration pathways exist. Model complexity increases exponentially as the number of possible migration pathways increases. Results:Program Branch was developed as freeware to allow users to construct multistate release-recapture models based on a schematic of the study design built with a graphic user interface (GUI). The GUI can be used not only to develop the underlying statistical likelihood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Annual movement rates were estimated for each population by using multistate release–recapture models in Program Branch (Pope et al. ), as detailed by Richins () and illustrated in Figure . Parameters and SEs were estimated using maximum likelihood.…”
Section: Methodsmentioning
confidence: 99%
“…Annual movement rates were estimated for each population by using multistate release–recapture models in Program Branch (Pope et al. ), as detailed by Richins () and illustrated in Figure . Parameters and SEs were estimated using maximum likelihood.…”
Section: Methodsmentioning
confidence: 99%
“…However, a comparison of overshoot fallback proportions of the two basic overshoot pathways (upstream of PRD or ICH) has not been conducted. Pope et al (2016) used a multi-state release-recapture model to estimate the overshoot fallback rates for Walla Walla River hatchery steelhead. While hatchery steelhead are subject to direct harvest, Pope et al (2016) reported overshoot return rates of 8.3% and 20.2% for Lower Granite Dam and PRD, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Pope et al (2016) used a multi-state release-recapture model to estimate the overshoot fallback rates for Walla Walla River hatchery steelhead. While hatchery steelhead are subject to direct harvest, Pope et al (2016) reported overshoot return rates of 8.3% and 20.2% for Lower Granite Dam and PRD, respectively. Because Walla Walla River steelhead that make it to Lower Granite Dam must migrate downstream past four dams in the SR to return to the Walla Walla River compared to between one and five dams in the UCR, these results are not directly comparable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation